2009
DOI: 10.1007/s10955-009-9826-x
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic Synchronisation of Model Microswimmers

Abstract: We define a model microswimmer with a variable cycle time, thus allowing the possibility of phase locking driven by hydrodynamic interactions between swimmers. We find that, for extensile or contractile swimmers, phase locking does occur, with the relative phase of the two swimmers being, in general, close to 0 or pi, depending on their relative position and orientation. We show that, as expected on grounds of symmetry, self T-dual swimmers, which are time-reversal covariant, do not phase-lock. We also discuss… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
26
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 35 publications
0
26
0
Order By: Relevance
“…This leads to swimming trajectories with sharp turns, analogous to the run-and-tumble mechanism used by bacteria (30). Our system can be used to gain more insight into this phenomenon, which would also be relevant in artificial swimmers (7,8). The model studied here can stabilize inphase motion with slight variations (21) and we expect this to be relevant in determining the conditions necessary to obtain inphase synchronization.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…This leads to swimming trajectories with sharp turns, analogous to the run-and-tumble mechanism used by bacteria (30). Our system can be used to gain more insight into this phenomenon, which would also be relevant in artificial swimmers (7,8). The model studied here can stabilize inphase motion with slight variations (21) and we expect this to be relevant in determining the conditions necessary to obtain inphase synchronization.…”
Section: Discussionmentioning
confidence: 79%
“…Coordinated motion is crucial for the effective functioning of cilia and flagella, the elements of eukaryotic cells implicated in generating fluid flows and motility (4). Hydrodynamic coupling is also important in natural and artificial microfluidic conditions (5,6) and low Reynolds number (Re) "microbot" swimmers (7,8). At the relevant scales and temperatures, it has the same magnitude as the random thermal forces; nevertheless, the synchronized states of e.g.…”
mentioning
confidence: 99%
“…For a collection of free swimmers, such as microorganisms [8], hydrodynamic interactions have been shown to lead to instabilities [9,10] that can result in complex dynamical behaviors [10,11]. In the context of simple microswimmer models where hydrodynamic interactions coupled to internal degrees of freedom can be studied with minimal complexity, it has been shown that the coupling could result in complex dynamical behaviors such as oscillatory bound states between two swimmers [12], and collective many-body swimming phases [13,14].A particularly interesting aspect of such hydrodynamic coupling is the possibility of synchronization between different objects with cyclic motions [4,5,[15][16][17][18][19][20][21]. This effect has mostly been studied in simple systems such as two interacting objects or linear arrays and very little is known about possible many-body emergent behaviors of a large number of active objects with hydrodynamic coupling.…”
mentioning
confidence: 99%
“…In this context, the swimming efficiency [33] of a Stokes swimmer [34][35][36][37] as a simple model of such propulsion with additional motional-degrees of freedom of a body of the microorganism beyond those of flagella would be worthy of further investigation. Developing the concise description of energy dissipation for more complicated collective dynamics, e.g., hydrodynamic synchronization of microswimmers [38] and cilia in metachronal coordination [9,39,40], will also be interesting. To this end, extensions of our theory so that it includes radial flexibility [19] with general orbital shapes [13,14] and the formulation for many-body systems will be required to achieve a more general formulation of the energetics of synchronization in coupled oscillators.…”
Section: Summary and Discussionmentioning
confidence: 99%